SHALINA TAMARA ISMAILOVNA (TO THE 70TH ANNIVERSARY SINCE BIRTH) - Irina A Bulankina; Vladimir G Izatulin; Irina N Gerasimova; Olga N Shashkov; Galina M Globenko; Anna N Sinelnikova (Байкальский медицинский журнал)
The head of the Department of Human Anatomy, Operative Surgery and Forensic Medicine of Irkutsk State Medical University, Doctor of Medical Sciences, Professor Tamara Ismailovna Shalina turned 70 years old. Tamara Ismailovna was born on May 5, 1954 in Cherkessk, Stavropol Territory. After graduating from school, she entered medical school and graduated with honors in 1975. Having worked as a paramedic in a medical and physical education clinic and in an anti-tuberculosis clinic, she realized that medicine was her calling and that she was most interested in preventive medicine and scientific research. Therefore, she decided to continue her studies and in 1979 she entered the sanitary and hygienic faculty of the Irkutsk State Medical Institute. After graduating from the institute in 1985, she was invited to the Department of Human Anatomy as an assistant, where she works to the present day.Teams of the departments of human anatomy, operative surgery and forensic medicine, histology, embryology, cytology, normal physiology, university staff and students warmly congratulate Tamara Ismailovna on her 70th birthday, wishing her good health, family well-being and further achievements in her career.